Snake bite-induced renal medullary angitiis in a child: A case report - Lesa Dawman (Saudi Journal of Kidney Diseases and Transplantation, 2019)
Snake bite envenomation is common in tropical countries during the summer. Snake bite-induced acute kidney injury (AKI) has varied histopathological manifestations such as acute cortical necrosis, acute tubular necrosis (ATN), and acute interstitial nephritis. However, snake bite-induced renal medullary angiitis has rarely been reported. We describe a nine-year-old child with AKI following viperine snake bite and renal biopsy revealed pigment cast nephropathy, ATN and medullary angiitis.